Cost‐effectiveness of implantable ventricular assist devices in older children with stable, inotrope‐dependent dilated cardiomyopathy. (22nd January 2021) - Avanceña, Anton L. V.; Hutton, David W.; Lee, Josie; Schumacher, Kurt R.; Si, Ming‐Sing; Peng, David M.
Abstract: Background: In a stable, inotrope‐dependent pediatric patient with dilated cardiomyopathy, we evaluated the cost‐effectiveness of continuous‐flow VAD implantation compared to a watchful waiting approach using chronic inotropic therapy. Methods: We used a state‐transition model to estimate the costs and outcomes of 14‐year‐old (INTERMACS profile 3) patients receiving either VAD or watchful waiting. We measured benefits in terms of lifetime QALYs gained. Model inputs were taken from the literature. We calculated the ICER, or the cost per additional QALY gained, of VADs and performed multiple sensitivity analyses to test how our assumptions influenced the results. Results: Compared to watchful waiting, VADs produce 0.97 more QALYs for an additional $156 639, leading to an ICER of $162 123 per QALY gained from a healthcare perspective. VADs have 17% chance of being cost‐effective given a cost‐effectiveness threshold of $100 000 per QALY gained. Sensitivity analyses suggest that VADs can be cost‐effective if the costs of implantation decrease or if hospitalization costs or mortality among watchful waiting patients is higher. Conclusions: As a bridge to transplant, VADs provide a health benefit to children who develop stable, inotrope‐dependent heart failure, but immediate implantation is not yet a cost‐effective strategy compared to watchful waiting based on commonly used cost‐effectiveness thresholds. Early VAD support can be cost‐effective in sicker patients and if device implantation is cheaper. In complex conditions such as pediatric heart failure, cost‐effectiveness should be just one of many factors that inform clinical decision‐making.